Motivations through Metaphor in 'Not Afraid' and 'Read All about It' - Amalia Ayu Windari; Heri Dwi Santoso (Universitas Muhammadiyah Semarang, 2018)
This study examined the figurative language in the lyrics of Eminem and Emili Sande songs. It will easier and more interesting to analyze the figurative language trough the literary work that people hear everyday such a song lyric. This research use descriptive qualitative method. The main sources of data in this research were the lyric song of Eminem's `Not Afraid` and Emili Sande's `Read All About It`. The analysis of the data used the following step: first, listen to the songs, found the printed lyric of the song, found the figurative language. The last, the researcher drew the conclusion of this study. The result of this study show that, both song lyric, use the metaphor and personification. Based on the figurative language analysis, the singer wants to declare something and give motivation to the reader or listener through these songs.